UNIVERSITY COMMUNITY ENGAGEMENT IN STRENGTHENING DIASPORA ECONOMIC ROLE: THE CASE OF BINUS UNIVERSITY AT THE JAVANESE DIASPORA INTERNATIONAL CONGRESS - Steelyana W, Evi; Witjaksono, Armanto; fathia rahmi, ismi; Waworuntu, Ine (Bina Nusantara University, 2026)
This article evaluates the contribution of higher education through community engagement at the Javanese Diaspora International Congress, with a case study of Binus University (School of Accounting). The study focuses on educational initiatives related to investment, taxation, and export–import as part of empowering the Javanese diaspora. A descriptive qualitative method was applied using content analysis of congress reports and media publications. Findings show that literacy in accounting, taxation, and investment facilitated by the university strengthens diaspora capacity in identifying economic opportunities while navigating Indonesia’s fiscal policy environment. The study contributes to the discourse on university community engagement by positioning it as a bridge between diaspora networks, government policy, and business development.